Differential Regulation of Genes Coding for Organelle and Cytosolic ClpATPases under Biotic and Abiotic Stresses in Wheat - Muthusamy, Senthilkumar K.; Dalal, Monika; Chinnusamy, Viswanathan; Bansal, Kailash C. (Frontiers in Plant Science, 2016)
A sub-group of class I Caseinolytic proteases (Clps) function as molecular chaperone and confer thermotolerance to plants. We identified class I Clp family consisting of five ClpB/HSP100, two ClpC and two ClpD genes from bread wheat. Phylogenetic analysis showed that these genes were highly conserved across grass genomes. Subcellular localization prediction revealed that TaClpC and TaClpD subgroup proteins and TaClpB1 proteins are potentially targeted to chloroplast, while TaClpB5 to mitochondria, and TaClpB2, TaClpB3 and TaClpB4 to cytoplasm. Spatio-temporal expression pattern analysis revealed that four TaClpB and TaClpD2 genes are expressed in majority of all tissues and developmental stages of wheat. Real-time RT-PCR analysis of expression levels of Clp genes in seven wheat genotypes under different abiotic stresses revealed that genes coding for the cytosolic Clps namely TaClpB2 and TaClpB3 were upregulated under heat, salt and oxidative stress but were downregulated by cold stress in most genotypes. In contrast, genes coding for the chloroplastic Clps TaClpC1, TaClpC2 and TaClpD1 genes were significantly upregulated by mainly by cold stress in most genotypes, while TaClpD2 gene was upregulated >2 fold by salt stress in DBW16. The TaClpB5 gene coding for mitochondrial Clp was upregulated in all genotypes under heat, salt and oxidative stresses. In addition, we found that biotic stresses also upregulated TaClpB4 and TaClpD1. Among biotic stresses, Tilletia caries induced TaClpB2, TaClpB3, TaClpC1 and TaClpD1. Differential expression pattern under different abiotic and biotic stresses and predicted differential cellular localization of Clps suggest their non-redundant organelle and stress-specific roles. Our results also suggest the potential role of Clps in cold, salt and biotic stress responses in addition to the previously established role in thermotolerance of wheat.